2022
DOI: 10.1371/journal.pone.0264977
|View full text |Cite
|
Sign up to set email alerts
|

Gluten-free diet exposure prohibits pathobiont expansion and gluten sensitive enteropathy in B cell deficient JH-/- mice

Abstract: In humans, celiac disease (CeD) is a T-cell-driven gluten-sensitive enteropathy (GSE) localized to the small bowel (duodenum). The presence of antibodies specific for gluten- and self-antigens are commonly used diagnostic biomarkers of CeD and are considered to play a role in GSE pathogenesis. Previously, we have described an apparent T-cell-mediated GSE in CD19-/- mice, which develop weak and abnormal B cell responses. Here, we expand on this observation and use a mouse model of complete B cell deficiency (JH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Previous studies from our lab support that primary antibody deficiency perturbs T cell homeostasis in the small bowel and that this may drive gut inflammation ( 18 , 19 ). Results from our analysis above are consistent with this.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Previous studies from our lab support that primary antibody deficiency perturbs T cell homeostasis in the small bowel and that this may drive gut inflammation ( 18 , 19 ). Results from our analysis above are consistent with this.…”
Section: Resultsmentioning
confidence: 55%
“…Thus, these latter differences are largely due to straindependent effects that are not shared drivers of immune dysregulation among mice. Previous studies from our lab support that primary antibody deficiency perturbs T cell homeostasis in the small bowel and that this may drive gut inflammation (18,19). Results from our analysis above are consistent with this.…”
Section: Pad-induced Immune Dysregulation Is Associated With Enhanced...mentioning
confidence: 65%
“…Mohammed et al. focused on the effect of gluten-free diet (GFD) on microbiota in B cell-deficient mice and found that it suppressed the expansion of anaerobic bacteria in the small intestine and colonization of the small intestine by a specific pathobiont ( 142 ).…”
Section: Microbiome-based Therapeutic Strategies In Ieimentioning
confidence: 99%
“…This finding provides new therapeutic perspectives in IgA-deficient patients based on intravenous immunoglobulin supplementation with IgG from IgA-deficient patient pools to offer better protection against gut bacterial translocations in patients with CVID (116). Mohammed et al focused on the effect of gluten-free diet (GFD) on microbiota in B cell-deficient mice and found that it suppressed the expansion of anaerobic bacteria in the small intestine and colonization of the small intestine by a specific pathobiont (142). Furthermore, other studies suggested metabolic byproducts from gut microbiota (e.g., SCFAs) could cause epigenetic modification by affecting the local homeostasis of phagocytes and myelopoiesis in the bone marrow.…”
Section: Microbiome-based Therapeutic Strategies In Ieimentioning
confidence: 99%
“…Previously, we demonstrated that CD19 −/− and JH −/− mice present with SIBO (which we defined as both total increases in bacterial biomass in the SI as well as altered taxonomic composition) [ 41 , 42 ]. We also demonstrated that this was associated with defects in bacterial BA metabolism [ 41 ].…”
Section: Introductionmentioning
confidence: 99%